Theoretical Analysis of Efficient Thermo-Optic Switching on Si3N4 Waveguide Platform Using SiOC-Based Plasmo-Photonics - Dimitris V. Bellas; Eleftheria Lampadariou; George Dabos; Ioannis Vangelidis; Laurent Markey; Jean-Claude Weeber; Nikos Pleros; Elefterios Lidorikis (Nanomaterials)
Photonic integrated circuits (PICs) are crucial for advanced applications in telecommunications, quantum computing, and biomedical fields. Silicon nitride (SiN)-based platforms are promising for PICs due to their transparency, low optical loss, and thermal stability. However, achieving efficient thermo-optic (TO) modulation on SiN remains challenging due to limited reconfigurability and high power requirements. This study aims to optimize TO phase shifters on SiN platforms to enhance power efficiency, reduce device footprint, and minimize insertion losses. We introduce a CMOS-compatible plasmo-photonic TO phase shifter using a SiOC material layer with a high TO coefficient combined with aluminum heaters on a SiN platform. We evaluate four interferometer architectures—symmetric and asymmetric Mach–Zehnder Interferometers (MZIs), an MZI with a ring resonator, and a single-arm design—through opto-thermal simulations to refine performance across power, losses, footprint, and switching speed metrics. The asymmetric MZI with ring resonator (A-MZI-RR) architecture demonstrated superior performance, with minimal power consumption (1.6 mW), low insertion loss (2.8 dB), and reduced length (14.4 μm), showing a favorable figure of merit compared to existing solutions. The optimized SiN-based TO switches show enhanced efficiency and compactness, supporting their potential for scalable, energy-efficient PICs suited to high-performance photonic applications.